2016
DOI: 10.1016/j.respol.2015.10.014
|View full text |Cite|
|
Sign up to set email alerts
|

The role of diversification profiles and dyadic characteristics in the formation of technological alliances: Differences between exploitation and exploration in a low-tech industry

Abstract: This paper posits that corporate and technological diversification of firms and their relatedness in terms of products and technologies will impact their propensity to form technological alliances. It argues that both higher levels of diversification and greater relatedness signal superior capabilities and available resources to prospective partners that will facilitate exploration and exploitation of technological assets in an alliance.These theoretical conjectures are tested using a dataset of all tire produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 112 publications
1
43
0
Order By: Relevance
“…There is much research in the field on the role of inter‐organizational relationships (Cantwell and Santangelo ; Krammer ; Quintana‐García and Benavides‐Velasco ). But future studies need to push further.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…There is much research in the field on the role of inter‐organizational relationships (Cantwell and Santangelo ; Krammer ; Quintana‐García and Benavides‐Velasco ). But future studies need to push further.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Research has therefore found that technological diversification has a positive association with entry into strategic alliances (Zhang et al . ), in particular explorative (for example R&D‐based) alliances (Krammer ). In the same study, Krammer found that exploitative (e.g.…”
Section: Empirical Research On Technological Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when analyzing the impact of innovation on economic competitiveness one must carefully account for systemic and industrial particularities that affect the creation, diffusion and exploitation of knowledge among different actors in these innovation systems (Todtling and Trippl, 2005;Krammer 2016). …”
Section: Systems-economic Competitiveness Nexusmentioning
confidence: 99%
“…These environments provide a far-less-than-ideal setting for implementing SS by suffering from low entrepreneurship rates (Carre and Thurik, 2008), weak systems of innovation (Krammer, 2009), limited technological opportunities (Krammer, 2016), significant institutional heterogeneity (Krammer, 2015a), lack of significant regional autonomy (Charles et al, 2012) and market-driven clusters (Bröchler and Kalentzis, 2017). Together, all these issues raise significant concerns regarding the successful implementation of SS strategies for such "laggard" regions or countries, particularly when targeting techno-economic development (Phillips et al, 2016).…”
Section: Conclusion Limitations and Future Agendamentioning
confidence: 99%